Cranberries for women with recurrent urinary tract infection: a meta-analysis (Medical Journal of Indonesia, 2019)
BACKGROUND Cranberries are the most widely used nonantibiotic prophylaxis for recurrent urinary tract infection (rUTI) in women; however, their efficacy still remains uncertain. Hence, this meta-analysis was aimed to assess the effectiveness, safety, and adherence of cranberry as a prophylactic drug for treating rUTI. METHODS Literature search was conducted using PubMed, EBSCO, Science Direct, Scopus, Cochrane, and Google Scholar. Studies were screened for duplication, inclusion and exclusion criteria, and then reviewed by two authors independently. This included all randomized controlled trials of cranberry derivatives versus placebo and antibiotic prophylaxis. Cochrane risk-of-bias assessment tools were used to evaluate the quality of the study. Quantitative analysis was performed using the Review Manager 5.0 software. RESULTS Nine studies were included. Among 1,542 participants, cranberry consumption reduced incidence of rUTI in women compared with placebo (p = 0.02). The subgroup analysis revealed that only cranberry capsules were superior to placebo (relative risk [RR] = 0.67, 95% confidence interval [CI] = 0.45-0.98), but not for cranberry juice (RR = 0.85, 95% CI: 0.7-1.04). Antibiotics had better outcome than cranberry for rUTI (RR = 0.83, 95% CI = 0.70-0.98). Most of the participants experienced minor adverse events such as rash and gastrointestinal symptoms. There was also a good adherence rate, ranging from 90.3-99% monthly dose. CONCLUSIONS Cranberry, especially cranberry capsule consumption, had a significant effect in reducing the incidence of rUTI compared with placebo, with good adherence rates, and minor adverse events. In contrast, although antibiotic use had a greater efficacy, it was associated with a higher risk of severe adverse events.